The Fiscal Roots of Financial Underdevelopment. Issue 2 (22nd December 2015) - Menaldo, Victor
Abstract : Abstract: Why do some countries indulge in financial repression, harming economic development in the process, whereas others promote financial development? Three main explanations have been put forth. Market failures, due to information asymmetries, mean that credit is rationed even when lenders could potentially benefit from making loans readily available. Political failures, due to state capture, mean that credit will be rationed as a way of generating rents for politically powerful financial incumbents. The state might, however, have its own fiscal reasons for politicizing the supply and price of credit, since financial repression provides easy‐to‐collect revenues. I draw on the third approach to argue that the state's fiscal imperative is usually the primary reason behind financial repression, and even when private actors benefit, they are subordinate to this concern. A dynamic panel analysis that exploits instrumental variables and a case study of Mexico adduce strong empirical support for my fiscal transaction cost theory . Replication Materials: The data, code, and any additional materials required to replicate all analyses in this article are available on the American Journal of Political Science Dataverse within the Harvard Dataverse Network, at:http://dx.doi.org/10.7910/DVN/WVQ10L .